'How do you reflect linguistic diversity in the classroom?': A quanticised analysis. The pedagogic repertoires of pre-service teachers in England training in predominantly monolingual classrooms. (3rd July 2022) - Bailey, Elizabeth G.
ABSTRACT: This study, undertaken in a predominantly monolingual area of England, examines pre-service teachers' ( N  = 293) suggestions of how they could reflect linguistic diversity in primary classrooms (ages 4-11). Trialling a mixed method approach where open-text data are quanticised, a combination of content analysis and statistical analysis are used to ask a) what methodsare identified as ways of reflecting linguistic and cultural diversity? And b) is there a difference in the methods suggested by the pre-service teachers according to their own experience of learning languages and the institution they train at? The methods most commonly suggsted were likely to be isolated events and fit with existing structures (e.g. "show and tell" time, multicultural days and guest speakers). Overall, substantial differences in pre-service teachers' pedagogic repertoires were found, highlighting the need to ensure practice, research and rhetoric supporting multilingualism reaches all.